DIGITALISASI UMKM SEBAGAI SOLUSI BERTAHAN DIMASA KRISIS PANDEMI COVID-19 - Khairina Natsir (PROSIDING SERINA, 2021)
Partners in this PKM activity are MSME actors located in RT 10/RW 04 Batan Indah Housing, Kademangan village, Setu district, South Tangerang. It is currently inhabited by around 45 families, of which 30% of the families are small business SMEs engaged in the culinary field, such as cakes, snacks, frozen products and other creative industries. The problem that occurred was that during the pandemic due to social restrictions, the sales turnover of culinary businesses decreased drastically to 75%, some even temporarily chose to take a break from selling activities because the buyers were very quiet, and as a result they lost money due to overstock of their merchandise. If these MSME partners are able to convert their business to digital, it is certain that these residents' culinary products will continue to run well, because the actual need for household culinary delights such as breakfast or side dishes for lunch at partner locations is still very high. This PKM activity aims to provide training/counseling on how to digitize sales and product promotions by utilizing available hardware and optimizing the use of existing social and business platforms such as WhatsApp for Business and Gofood. The benefits obtained by digitizing products are to reach sales and a wider market even during a pandemic. The activity has been carried out from 7 November 2021 to 20 November 2021. As many as 15 business actors were visited one by one and given counseling and dialogue about the digitization of MSMEs and an explanation of the use of the WhatsApp Business application and the installation of GoFood on HP. The activity went smoothly and the material was conveyed quite completely.